Cerebrospinal fluid and plasma biomarker trajectories with increasing amyloid deposition in Alzheimer's disease. Issue 12 (11th November 2019) - Palmqvist, Sebastian; Insel, Philip S; Stomrud, Erik; Janelidze, Shorena; Zetterberg, Henrik; Brix, Britta; Eichenlaub, Udo; Dage, Jeffrey L; Chai, Xiyun; Blennow, Kaj; Mattsson, Niklas; Hansson, Oskar
Abstract: Failures in Alzheimer's disease (AD) drug trials highlight the need to further explore disease mechanisms and alterations of biomarkers during the development of AD. Using cross‐sectional data from 377 participants in the BioFINDER study, we examined seven cerebrospinal fluid (CSF) and six plasma biomarkers in relation to β‐amyloid (Aβ) PET uptake to understand their evolution during AD. In CSF, Aβ42 changed first, closely followed by Aβ42/Aβ40, phosphorylated‐tau (P‐tau), and total‐tau (T‐tau). CSF neurogranin, YKL‐40, and neurofilament light increased after the point of Aβ PET positivity. The findings were replicated using Aβ42, Aβ40, P‐tau, and T‐tau assays from five different manufacturers. Changes were seen approximately simultaneously for CSF and plasma biomarkers. Overall, plasma biomarkers had smaller dynamic ranges, except for CSF and plasma P‐tau which were similar. In conclusion, using state‐of‐the‐art biomarkers, we identified the first changes in Aβ, closely followed by soluble tau. Only after Aβ PET became abnormal, biomarkers of neuroinflammation, synaptic dysfunction, and neurodegeneration were altered. These findings lend in vivo support of the amyloid cascade hypotheses in humans. Synopsis: Analysis of the evolution of 13 key cerebrospinal and plasma biomarkers in relation to increasing Aβ accumulation during Alzheimer's disease confirms the amyloid hypothesis, and highlight the presence of other disease mechanisms already prior to the threshold for amyloid positivity. Failures in Alzheimer's disease (AD) drug trials highlight the need to further explore disease mechanisms and alterations of biomarkers during the development of AD. The study examines seven cerebrospinal fluid (CSF) and six plasma biomarkers in relation to β‐amyloid (Aβ) PET uptake to understand their evolution during AD. The first changes were seen in Aβ biomarkers, closely followed by soluble tau, and then approximately simultaneously in markers of neuroinflammation, synaptic dysfunction and neurodegeneration. The results were replicated using five different CSF assays for Aβ42, Aβ40, P‐tau and T‐tau. Abstract : Analysis of the evolution of 13 key cerebrospinal and plasma biomarkers in relation to increasing Aβ accumulation during Alzheimer's disease confirms the amyloid hypothesis, and highlight the presence of other disease mechanisms already prior to the threshold for amyloid positivity.